Evaluating the analytical performance of five new coagulation assays for the measurement of prothrombin time and activated thromboplastin time. (22nd July 2018) - Kitchen, Steve; Geisen, Ulrich; Kappelmayer, Janos; Quehenberger, Peter; Drieß, Julia; Lowe, Anna; Jones, Robert; Boehm, Jana G.; Miles, Gabrielle; Rozsnyai, Gergely
Abstract: Introduction: New methods for coagulation tests require careful assessment before routine use. We evaluated the analytical performance of five new coagulation assays for measuring prothrombin time (PT) and activated partial thromboplastin time (aPTT). Methods: PT Rec, PT Owren, aPTT, aPTT Lupus and aPTT Screen assays (Roche Diagnostics) were evaluated oncobas t 711 andcobas t 511 analysers (Roche Diagnostics) at four European centres. Analytical performance and method comparisons with relevant commercially available assays were performed to Clinical Laboratory Standards Institute guidelines using residual anonymized samples. Lot‐to‐lot comparison and equivalency of thecobas t analysers were also assessed; reference ranges were determined using samples from apparently healthy volunteers. Results: Overall, coefficients of variation were ≤1.3% for within‐run precision and ≤6.3% for total reproducibility across all sites. Deming regression analyses showed good agreement between each assay (cobas t 711) and respective comparator method (Pearson's r : 0.964‐0.999, n > 120 samples/assay/site). Passing–Bablok regression analyses demonstrated equivalence of the twocobas t platforms for use with each assay (Pearson's r  ≥ 0.995). Lot‐to‐lot consistency was high for all assays and comparisons (Pearson's r  ≥ 0.998). Reference ranges (2.5th‐97.5th percentiles; n = 200 samples/assay) in seconds were 8.4‐10.6 (PT Rec), 18.2‐27.2 (PT Owren), 23.6‐30.6 (aPTT), 24.1‐31.7 (aPTT Lupus) and 23.9‐33.2 (aPTT Screen). Conclusion: Based on the excellent analytical performance and good agreement with relevant comparator methods, the five coagulation assays on the novelcobas t 711 andcobas t 511 analysers are suitable for routine use in core laboratories.